The social resilience of fishermen to oral diseases during the covid-19 pandemic in puger jember east java - Komarudin, Koko; Mashud, Mustain; Andriati, Retno; Apriasari, Maharani Laillyza (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Puger fishermen are able to survive and develop (resilience) in carrying out their activities in the form of natural disturbances and various diseases, especially during the COVID-19 pandemic. Oral diseases are the lowest of the seven diseases recorded at the Puger Health Center. This disease can make patients exposed to COVID-19 worse, but the Puger area is included in the green zone. The Purpose of this study is to analyze the effect of knowledge, behavior and health services to the social resilience ability of Puger fishermen.Method: It used a quantitative approach with the method of structural equation modelling (SEM). Confirmatory factor analysis tests and path analysis were conducted to analyze the effect among variables according to the research purpose. Questionnaires were distributed to fishermen who were sampled as respondents. Respondents amounted to 111 people. It used is simple random sampling.Result: The knowledge has a positive effect, but it is not significant to social resilience with a significance level (Î²= 0.001 p: 0.314>0.05), behavior has a positive effect, but it is not significant to social resiliance with a significance level (Î²= 0.005 p: 0.649>0.05) and Health service has a positive effect, but it is not significant to social resilience with a significance level (Î²= 0.003 p: 0.218>0.05).Conclusion: Puger Fishermen has social resilience ability to oral diseases underpinned by knowledge, behavior as well as health service. These variables have a positive correlation with resilience. Yet the level is not quite significant.